2004
DOI: 10.1086/382719
|View full text |Cite
|
Sign up to set email alerts
|

Northern Sky Variability Survey: Public Data Release

Abstract: The Northern Sky Variability Survey (NSVS) is a temporal record of the sky over the optical magnitude range from 8 to 15.5. It was conducted in the course of the first-generation Robotic Optical Transient Search Experiment (ROTSE-I) using a robotic system of four comounted unfiltered telephoto lenses equipped with CCD cameras. The survey was conducted from Los Alamos, New Mexico, and primarily covers the entire northern sky. Some data in southern fields between declinations 0 and À38 are also available, althou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
212
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 478 publications
(215 citation statements)
references
References 25 publications
3
212
0
Order By: Relevance
“…To estimate the source variability of the S-type stars, we have cross-identified all stars in the GCSS2 with the two major available variability surveys: the All Sky Automated Survey (ASAS) located at the Las Campanas Observatory (Pojmanski et al 2005) and the Northern Sky Variability Survey 3 (NSVS) operated at Los Alamos National Laboratory (Woźniak et al 2004a). This resulted in 1154 S-type stars with V-band light curves.…”
Section: Sample Selectionmentioning
confidence: 99%
“…To estimate the source variability of the S-type stars, we have cross-identified all stars in the GCSS2 with the two major available variability surveys: the All Sky Automated Survey (ASAS) located at the Las Campanas Observatory (Pojmanski et al 2005) and the Northern Sky Variability Survey 3 (NSVS) operated at Los Alamos National Laboratory (Woźniak et al 2004a). This resulted in 1154 S-type stars with V-band light curves.…”
Section: Sample Selectionmentioning
confidence: 99%
“…Numerical constants were adopted from Woźniak et al (2004). Prior to the analysis the light curves from individual observatories/instruments were corrected for small magnitude offsets, with the light curve from WASP being taken as the reference.…”
Section: Photometric Observationsmentioning
confidence: 99%
“…Early coverage of HS0705 and NSVS1425 is available from archival data of the Northern Sky Variability Survey (Woźniak et al 2004) 1 , which provides short glimpses of the sky for an extended period of time in 1999, with exposure times between 20 and 80 s. HS0705 was extensively studied from October 2000 on by Drechsel et al (2001). The source was subsequently monitored by Qian et al (2009Qian et al ( , 2010a, and references therein).…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…NSVS 14256825 (in short NSVS1425) was discovered as a 13.2 mag variable star in the Northern Sky Variability Survey (Woźniak et al 2004) and identified as an eclipsing binary with a 2.6 h orbital period and an sdB primary by Wils et al (2007). The source seems to be in many respects a twin of HS0705 and the prototype sdB/M-dwarf binary HW Vir (Lee et al 2009).…”
Section: Introductionmentioning
confidence: 99%